Disruption of Vitamin D and Calcium Signaling in Keratinocytes Predisposes to Skin Cancer - Bikle, Daniel D.; Jiang, Yan; Nguyen, Thai; Oda, Yuko; Tu, Chia-ling (Frontiers in Physiology, 2016)
1,25 dihydroxyvitamin D (1,25(OH)2D), the active metabolite of vitamin D, and calcium regulate epidermal differentiation. 1,25(OH)2D exerts its effects through the vitamin D receptor (VDR), a transcription factor in the nuclear hormone receptor family, whereas calcium acts through the calcium sensing receptor (Casr), a membrane bound member of the G protein coupled receptor family. We have developed mouse models in which the Vdr and Casr have been deleted in the epidermis (epidVdr-/- and epidCasr-/-). Both genotypes show abnormalities in calcium induced epidermal differentiation in vivo and in vitro, associated with altered hedgehog (HH) and beta-catenin signaling that when abnormally expressed lead to basal cell carcinomas (BCC) and trichofolliculomas, respectively. The Vdr-/- mice are susceptible to tumor formation following UVB or chemical carcinogen exposure. More recently we found that the keratinocytes from these mice over express long noncoding RNA (lncRNA) oncogenes such as H19 and under express lncRNA tumor suppressors such as lincRNA-21. Spontaneous tumors have not been observed in either the epidVdr-/- or epidCasr-/-. But in mice with epidermal specific deletion of both Vdr and Casr (epidVdr-/- / epidCasr-/- [DKO]) tumor formation occurs spontaneously when the DKO mice are placed on a low calcium diet. These results demonstrate important interactions between vitamin D and calcium signaling through their respective receptors that lead to cancer when these signals are disrupted. The roles of the beta catenin, hedgehog, and lncRNA pathways in predisposing the epidermis to tumor formation when vitamin D and calcium signaling are disrupted will be discussed.